Health education of Covid-19 vaccination program for tourism industry - Rosalina, Linda; Marlina, Hastuti; Yuliana, Yuliana; Mentari, Tyas Asih; Renaldi, Reno (International Journal of Research in Counseling and Education, 2022)
One of the efforts taken by the government to help people boost their immunity and prevent transmission is the Covid vaccination program. There are a number of government entities that collaborate with local institutions to distribute vaccines to the general public. Tourism's long-term sustainability is dependent on good health. However, the difficulty is that the community, in general, and tourism actors, in particular, continue to oppose the implementation of this program. There are different causes, and challenges that make some community members reject this initiative. These issues must be addressed, and one way to do so is through health education. This activity was carried out utilizing a mixed method approach, with data collected through observation, interviews, and questionnaires. The community in Jorong Aie Malanca, Nagari Harau, Payakumbuh is the object of the activity. The implementation of the activities collected demonstrated that the community is enthusiastic about vaccination; although information about the ease and safety of vaccines is still insufficient, this program has been successful in assisting the community in overcoming these issues.